Sold on a Monday (Recorded Books, Inc., Sourcebooks Inc, Sourcebooks, Sourcebooks Landmark, 2018)
2 CHILDREN FOR SALE The sign is a last resort. It sits on a farmhouse porch in 1931, but could be found anywhere in an era of breadlines, bank runs and broken dreams. It could have been written by any mother facing impossible choices. For struggling reporter Ellis Reed, the gut-wrenching scene evokes memories of his family's dark past. He snaps a photograph of the children, not meant for publication. But when it leads to his big break, the consequences are more devastating than he ever imagined. At the paper, Lillian Palmer is haunted by her role in all that happened. She is far too familiar with the heartbreak of children deemed unwanted. As the bonds of motherhood are tested, she and Ellis must decide how much they are willing to risk to mend a fractured family. Inspired by an actual newspaper photograph that stunned the nation, Sold on a Monday is a powerful novel of love, redemption, and the unexpected paths that bring us home.

The Girl in His Shadow: A Novel (Recorded Books, Inc., Sourcebooks Inc, Sourcebooks, 2021)
THE USA TODAY BESTSELLER! "An exquisitely detailed journey through the harrowing field of medicine in mid-19th century London."—Tracey Enerson Wood, USA Today bestselling author of The Engineer's Wife and The War Nurse An unforgettable historical fiction novel about one woman who believed in scientific medicine before the world believed in her. London, 1845: Raised by the eccentric surgeon Dr. Horace Croft after losing her parents to a deadly pandemic, the orphan Nora Beady knows little about conventional life. While other young ladies were raised to busy themselves with needlework and watercolors, Nora was trained to perfect her suturing and anatomical illustrations of dissections. Women face dire consequences if caught practicing medicine, but in Croft's private clinic Nora is his most trusted—and secret—assistant. That is until the new surgical resident Dr. Daniel Gibson arrives. Dr. Gibson has no idea that Horace's bright and quiet young ward is a surgeon more qualified and ingenuitive than even himself. In order to protect Dr. Croft and his practice from scandal and collapse Nora must learn to play a new and uncomfortable role—that of a proper young lady. But pretense has its limits. Nora cannot turn away and ignore the suffering of patients, even if it means giving Gibson the power to ruin everything she's worked for. And when she makes a discovery that could change the field forever, Nora faces an impossible choice. Remain invisible and let the men around her take credit for her work, or step into the light—even if it means being destroyed by her own legacy. Fans of The Other Einstein and The Paris Library will relish this riveting and empowering story about one woman's fight to follow her dreams and build a life—and legacy—beyond what is expected of her. Praise for The Girl in His Shadow: "A suspenseful story of a courageous young woman determined to become a surgeon in repressive Victorian England. Fluidly written, impeccably researched, The Girl in His Shadow is a memorable literary gift to be read, reread, and treasured."—Gloria Goldreich, author of The Paris Children Other Bestselling Historical Fiction from Sourcebooks Landmark: The Mystery of Mrs. Christie by Marie Benedict The Book Woman of Troublesome Creek by Kim Michele Richardson Sold on a Monday by Kristina McMorris

A column of fire (Kingsbridge, 3,, 2017)
"International bestselling author Ken Follett has enthralled millions of readers with The Pillars of the Earth and World Without End, two stories of the Middle Ages set in the fictional city of Kingsbridge. The saga now continues with Follett's magnificent new epic, A Column of Fire. In 1558, the ancient stones of Kingsbridge Cathedral look down on a city torn apart by religious conflict. As power in England shifts precariously between Catholics and Protestants, royalty and commoners clash, testing friendship, loyalty, and love. Ned Willard wants nothing more than to marry Margery Fitzgerald. But when the lovers find themselves on opposing sides of the religious conflict dividing the country, Ned goes to work for Princess Elizabeth. When she becomes queen, all Europe turns against England. The shrewd, determined young monarch sets up the country's first secret service to give her early warning of assassination plots, rebellions, and invasion plans. Over a turbulent half century, the love between Ned and Margery seems doomed as extremism sparks violence from Edinburgh to Geneva. Elizabeth clings to her throne and her principles, protected by a small, dedicated group of resourceful spies and courageous secret agents"--

The Book Woman of Troublesome Creek: A Novel (Sourcebooks Inc, Sourcebooks, Blackstone Publishing, 2019)
RECOMMENDED BY DOLLY PARTON IN PEOPLE MAGAZINE! A NEW YORK TIMES BESTSELLER A USA TODAY BESTSELLER A LOS ANGELES TIMES BESTSELLER The bestselling historical fiction novel from Kim Michele Richardson, this is a novel following Cussy Mary, a packhorse librarian and her quest to bring books to the Appalachian community she loves, perfect for readers of William Kent Kreuger and Lisa Wingate. The perfect addition to your next book club! The hardscrabble folks of Troublesome Creek have to scrap for everything—everything except books, that is. Thanks to Roosevelt's Kentucky Pack Horse Library Project, Troublesome's got its very own traveling librarian, Cussy Mary Carter. Cussy's not only a book woman, however, she's also the last of her kind, her skin a shade of blue unlike most anyone else. Not everyone is keen on Cussy's family or the Library Project, and a Blue is often blamed for any whiff of trouble. If Cussy wants to bring the joy of books to the hill folks, she's going to have to confront prejudice as old as the Appalachias and suspicion as deep as the holler. Inspired by the true blue-skinned people of Kentucky and the brave and dedicated Kentucky Pack Horse library service of the 1930s, The Book Woman of Troublesome Creek is a story of raw courage, fierce strength, and one woman's belief that books can carry us anywhere—even back home. Look for The Book Woman's Daughter, the new novel from Kim Michele Richardson, out now! Other Bestselling Historical Fiction from Sourcebooks Landmark: The Mystery of Mrs. Christie by Marie Benedict The Engineer's Wife by Tracey Enerson Wood Sold on a Monday by Kristina McMorris

Carnegie's Maid: A Novel (Sourcebooks Inc, Sourcebooks, 2018)
The USA Today Bestseller From the bestselling author of The Only Woman in the Room comes a mesmerizing tale of historical fiction that asks what kind of woman could have inspired an American dynasty. Clara Kelley is not who they think she is. She's not the experienced Irish maid who was hired to work in one of Pittsburgh's grandest households. She's a poor farmer's daughter with nowhere to go and nothing in her pockets. But the woman who shares her name has vanished, and assuming her identity just might get Clara some money to send back home. Clara must rely on resolve as strong as the steel Pittsburgh is becoming famous for and an uncanny understanding of business, attributes that quickly gain her Carnegie's trust. But she still can't let her guard down, not even when Andrew becomes something more than an employer. Revealing her past might ruin her future—and her family's. With captivating insight and heart, Carnegie's Maid is a book of fascinating 19th century historical fiction. Discover the story of one brilliant woman who may have spurred Andrew Carnegie's transformation from ruthless industrialist to the world's first true philanthropist. Other Bestselling Historical Fiction from Marie Benedict: The Mystery of Mrs. Christie Lady Clementine The Only Woman in the Room The Other Einstein

Before We Were Yours: A Novel (Random House Publishing Group, Books on Tape, 2017)
THE BLOCKBUSTER HIT—Over two million copies sold! A New York Times, USA Today, Wall Street Journal, and Publishers Weekly Bestseller “Poignant, engrossing.”—People • “Lisa Wingate takes an almost unthinkable chapter in our nation’s history and weaves a tale of enduring power.”—Paula McLain Memphis, 1939. Twelve-year-old Rill Foss and her four younger siblings live a magical life aboard their family’s Mississippi River shantyboat. But when their father must rush their mother to the hospital one stormy night, Rill is left in charge—until strangers arrive in force. Wrenched from all that is familiar and thrown into a Tennessee Children’s Home Society orphanage, the Foss children are assured that they will soon be returned to their parents—but they quickly realize the dark truth. At the mercy of the facility’s cruel director, Rill fights to keep her sisters and brother together in a world of danger and uncertainty. Aiken, South Carolina, present day. Born into wealth and privilege, Avery Stafford seems to have it all: a successful career as a federal prosecutor, a handsome fiancé, and a lavish wedding on the horizon. But when Avery returns home to help her father weather a health crisis, a chance encounter leaves her with uncomfortable questions and compels her to take a journey through her family’s long-hidden history, on a path that will ultimately lead either to devastation or to redemption. Based on one of America’s most notorious real-life scandals—in which Georgia Tann, director of a Memphis-based adoption organization, kidnapped and sold poor children to wealthy families all over the country—Lisa Wingate’s riveting, wrenching, and ultimately uplifting tale reminds us how, even though the paths we take can lead to many places, the heart never forgets where we belong. Publishers Weekly’s #3 Longest-Running Bestseller of 2017 • Winner of the Southern Book Prize • If All Arkansas Read the Same Book Selection This edition includes a new essay by the author about shantyboat life.

Notorious: A Thrilling Historical Regency Romance Saga (Rebels of the Ton, ,, 2020)
A PopSugar Best New Romance of November A She Reads Fall Historical Romance Pick A Bookclubz Recommended Read "Unique characters and emotional depth...a winner. Spencer gives you all the feels!" —Sabrina Jeffries "Brilliantly crafted...an irresistible cocktail of smart characterization, sophisticated sensuality, and sharp wit." —Booklist STARRED REVIEW "Sparkling...impossible not to love." —Popsugar Fans of Evie Dunmore, Sarah MacLean, and Eloisa James will delight in this innovative, empowering, and sexy story from acclaimed author Minerva Spencer. Join the Rebels of the Ton as they subvert Regency norms and expectations...and manage to find true love along the way. The cure for a willful wife . . . Drusilla Clare is full of opinions about why a woman shouldn't marry. But that doesn't stop the rush of desire she feels each time her best friend's brother, notorious rake Gabriel Marlington, crosses her path. So imagine her dismay when she finds herself in the clutches of a scoundrel, only to be rescued by Gabriel himself. And when Gabriel's heartless—and heart-pounding—proposal comes, it's enough to make Dru's formidable resolve crumble . . . . . . is a smitten husband. She's sharp-tongued, exasperating—and due to one careless moment—about to become his wife. Still, something about Drusilla has Gabriel intrigued. First there's the delicious flush of her skin every time she delivers a barb—and then the surprisingly sensual feel of her in his arms. Gabriel even finds himself challenged by her unusual philosophies. And when he discovers a clandestine rival for Dru's affection, his temperature flares even hotter. But the real threat to their happiness is one neither of the newlyweds sees coming. If they're to save their future—and their very lives—they'll need to trust in each other and their growing love. "Packed full of fiery exchanges and passionate embraces, this is for those who prefer their Regencies on the scandalous side." —Library Journal "Strong, complex, and believable." —Publishers Weekly

Shadows of Swanford Abbey (Recorded Books, Inc., Baker Publishing Group, 2021)
News of her brother's worrisome behavior spurs Miss Rebecca Lane to return home to her village. Upon her arrival, he begs her to go to nearby Swanford Abbey, a medieval monastery turned grand hotel rumored to be haunted. Feeling responsible for her brother's desperate state, she reluctantly agrees to stay at the abbey until she can deliver his manuscript to a fellow guest who might help him get published-an author who once betrayed them. Soon, Rebecca starts seeing strange things, including a figure in a hooded black gown gliding silently through the abbey's cloisters at night. For all its renovations and veneer of luxury, the ancient foundations seem to echo with whispers of the past-including her own. For there she encounters Sir Frederick-baronet, magistrate, and former neighbor-who long ago broke her heart. Now a handsome widower of thirty-five, he is trying to overcome a past betrayal of his own. When the famous author is found dead, Sir Frederick makes inquiries and quickly discovers that several people held grudges against the author, including Miss Lane and her brother. As Sir Frederick searches for answers, he is torn between his growing feelings for Rebecca and his pursuit of the truth. For Miss Lane is clearly hiding something...

A Duke, the Lady, and a Baby (Rogues and Remarkable Women, ,, 2020)
"Smart and witty . . . the perfect historical read." —Julia Quinn, #1 New York Times bestselling author New York Public Library, Bookriot, Vulture, Time Out, and Overdrive Featured Book to Read After Bridgerton! Featured in Entertainment Weekly, O Magazine, Washington Post, Wall Street Journal, Bustle, and Bookish! An Amazon Best of the Month Selection A Publishers Weekly Summer Reads 2020 Editors' Pick A ground-breaking, empowering, and sexy story from acclaimed author Vanessa Riley that fans of Beverly Jenkins, Evie Dunmore, and Alyssa Cole won't be able to put down. Join these Rogues & Remarkable Women as they fight for their status, their families...and true love. When headstrong West Indian heiress Patience Jordan questioned her English husband's mysterious suicide, she lost everything: her newborn son, Lionel, her fortune—and her freedom. Falsely imprisoned, she risks her life to be near her child—until The Widow's Grace gets her hired as her own son's nanny. But working for his unsuspecting new guardian, Busick Strathmore, Duke of Repington, has perils of its own. Especially when Patience discovers his military strictness belies an ex-rake of unswerving honor—and unexpected passion . . . A wounded military hero, Busick is determined to resolve his dead cousin's dangerous financial dealings for Lionel's sake. But his investigation is a minor skirmish compared to dealing with the forthright, courageous, and alluring Patience. Somehow, she's breaking his rules, and sweeping past his defenses. Soon, between formidable enemies and obstacles, they form a fragile trust—but will it be enough to save the future they long to dare together? "Vanessa Riley at her finest." —Sarah MacLean, New York Times bestselling author "I was delighted. Readers on the lookout for Black or disabled characters in historical romance will not want to miss this." —New York Times Book Review "One of the best historicals I've read in years." —Kristan Higgins, New York Times bestselling author "Expertly crafted romance." —Publishers Weekly, STARRED review

Murder on Black Swan Lane (Wrexford and Sloane Mystery, ,, 2017)
In Regency London, an unconventional scientist and a fearless female artist team up to trap a cold-hearted killer: "Thoroughly enjoyable" (Deanna Raybourn, New York Times–bestselling author). The Earl of Wrexford possesses a brilliant scientific mind, but boredom and pride lead him to reckless behavior. So when pompous, pious Reverend Josiah Holworthy publicly condemns him for debauchery, Wrexford unsheathes his rapier-sharp wit and strikes back. As their war of words escalates, London's most popular satirical cartoonist, A.J. Quill, skewers them both. But then the clergyman is found slain in a church—his face burned by chemicals, his throat slashed ear to ear—and Wrexford finds himself the chief suspect. An artist in her own right, Charlotte Sloane has secretly slipped into the persona of her late husband, using his nom de plume, A.J. Quill. When Wrexford discovers her true identity, she fears it will be her undoing. But he has a proposal—use her sources to unveil the clergyman's clandestine involvement in questionable scientific practices, and unmask the real murderer. Soon Lord Wrexford and the mysterious Mrs. Sloane plunge into a dangerous shadow world hidden among London's intellectual enclaves to trap a cunning adversary—before they fall victim to the next experiment in villainy . . . "Sharp, engaging characters, rich period detail, and a compellingly twisty plot, Andrea Penrose delivers a winner." —Deanna Raybourn, New York Times–bestselling author "Fans of C.S. Harris take note! A riveting ride through Regency London, from the slums of St. Giles, to the mansions of Mayfair." —Lauren Willig, New York Times–bestselling author "Historical chemistry meets alchemy . . . A delight of a book.&rdquo

A Reliable Wife (Recorded Books, Inc., Algonquin Books, 2009)
Rural Wisconsin, 1909. In the bitter cold, Ralph Truitt, a successful businessman, stands alone on a train platform waiting for the woman who answered his newspaper advertisement for "a reliable wife." But when Catherine Land steps off the train from Chicago, she's not the "simple, honest woman" that Ralph is expecting. She is both complex and devious, haunted by a terrible past and motivated by greed. Her plan is simple: she will win this man's devotion, and then, ever so slowly, she will poison him and leave Wisconsin a wealthy widow. What she has not counted on, though, is that Truitt - a passionate man with his own dark secrets -has plans of his own for his new wife. Isolated on a remote estate and imprisoned by relentless snow, the story of Ralph and Catherine unfolds in unimaginable ways. With echoes of Wuthering Heights and Rebecca, Robert Goolrick's intoxicating debut novel delivers a classic tale of suspenseful seduction, set in a world that seems to have gone temporarily off its axis. In addition to his most recent novel, The Fall of Princes, Robert Goolrick is the author of three other books: The End of the World as We Know It, a memoir; his first novel, A Reliable Wife, with sales of more than 1 million copies; and his second novel, Heading Out to Wonderful. He lives in Virginia. "After breaking through with a disquieting memoir . . . Goolrick applies his storytelling talents to a debut novel, set in 1907, about icy duplicity and heated vengeance. . . . A sublime murder ballad that doesn't turn out at all the way one might expect." -Kirkus, starred review-Publishers Weekly A Reliable Wife "generates some real suspense . . .This darkly nuanced psychological tale builds to a strong and satisfying close." –Publishers Weekly-Christian Science Monitor "Debut novelist Robert Goolrick has managed a minor miracle. In the kind of precise, literary prose that breathes life into his complicated characters, Goolrick, author of an acclaimed memoir, has also managed a rousing historical potboiler, an organic mystery rooted in the real social ills of turn-of-the-century America. Whether writing about the farms of Wisconsin or the fleshpots of St. Louis, he re-creates a full-bodied, believable environment, and he peoples these worlds with characters as sensitive, as tortured as any contemporary souls. The result is a detailed exploration of love, despair, and the distance people can travel to reach each other that is as surprising, and as suspenseful, as any beach read." -- Boston Globe-BookPage A "glittering, poisoned ice cube of a tale . . . Has a little of the Gothic feel of Daphne DuMaurier's Rebecca--complete with a dead first wife, suspicious housekeeper, and gorgeous mansion . . . A Reliable Wife is eminently readable and should delight fans of old-fashioned Gothic romances . . . Goolrick is a solid wordsmith, and he handily manages the impressive task of making readers care about a woman bent on cold-blooded murder. And generating the proper Gothic ambience in Wisconsin is no mean feat." -- Christian Science Monitor-Time Out New York A "fierce and sophisticated debut novel . . . In its best moments, A Reliable Wife calls to mind the chilling tales of Poe and Stephen King, and at its core this is a tragedy of Shakespearean dimensions. It melds a plot drenched in suspense with expertly realized characters and psychological realism. The fate of those characters is in doubt right up to this relentless story's intense final pages, and Goolrick's ability to sustain that tension is a tribute to his craftsmanship and one of the true pleasures of a fine first novel." -- Bookpage-Chicago Sun-Times "A weighty psychodrama laced with Hitchcockian suspense."-- Time Out New York -USA Today "[A] beautifully written, beautifully dark book. Goolrick is a superb writer."-Chicago Sun-Times -Washington Post "A killer debut novel . . . suspenseful and erotic . . .

Is This Tomorrow: A Novel (HighBridge, Algonquin Books, 2013)
Leavitt’s new novel, Days of Wonder, is coming April 23, 2024. Pre-order now! In 1956, Ava Lark rents a house with her twelve-year-old son, Lewis, in a desirable Boston suburb. Ava is beautiful, divorced, Jewish, and a working mom. She finds her neighbors less than welcoming. Lewis yearns for his absent father, befriending the only other fatherless kids: Jimmy and Rose. One afternoon, Jimmy goes missing. The neighborhood—in the throes of Cold War paranoia—seizes the opportunity to further ostracize Ava and her son. Years later, when Lewis and Rose reunite to untangle the final pieces of the tragic puzzle, they must decide: Should you tell the truth even if it hurts those you love, or should some secrets remain buried?

The Other Einstein: A Novel (Sourcebooks Inc, Sourcebooks, 2016)
From beloved New York Times and USA Today bestselling author Marie Benedict comes the story of a not-so-famous scientist who not only loved Albert Einstein, but also shaped the theories that brought him lasting renown. In the tradition of Beatriz Williams and Paula McClain, Marie Benedict's The Other Einstein offers us a window into a brilliant, fascinating woman whose light was lost in Einstein's enormous shadow. This novel resurrects Einstein's wife, a brilliant physicist in her own right, whose contribution to the special theory of relativity is hotly debated. Was she simply Einstein's sounding board, an assistant performing complex mathematical equations? Or did she contribute something more? Mitza Maric has always been a little different from other girls. Most twenty-year-olds are wives by now, not studying physics at an elite Zurich university with only male students trying to outdo her clever calculations. But Mitza is smart enough to know that, for her, math is an easier path than marriage. Then fellow student Albert Einstein takes an interest in her, and the world turns sideways. Theirs becomes a partnership of the mind and of the heart, but there might not be room for more than one genius in a marriage. Marie Benedict illuminates one pioneering woman in STEM, returning her to the forefront of history's most famous scientists. "The Other Einstein takes you into Mileva's heart, mind, and study as she tries to forge a place for herself in a scientific world dominated by men."—Bustle Recommended by PopSugar, Bustle, Booklist, Library Journal and more! Other Bestselling Historical Fiction from Marie Benedict: The Mystery of Mrs. Christie The Only Woman in the Room Lady Clementine Carnegie's Maid

Once a soldier (Thorndike Press large print romance, ,, 2016)
As heir to a title and great wealth, Will Masterson should have stayed home and tended his responsibilities. Instead he went to war. Now, after perilous years fighting the French, he intends his current mission to be his last. But all his plans are forgotten when he arrives in the small mountain stronghold of San Gabriel and meets her. Knowing herself to be too tall, strong, and unconventional to appeal to a man, Athena Markham has always gloried in her independence. But for the first time in her life, she finds a man who might be her match. Two of a kind, too brave for their own good, Athena and Will vow to do whatever it takes to vanquish San Gabriel's enemies. For neither will back down from death, and only together can they find happiness and a love deeper than any they'd dared imagine.

The Bargain (Regency, ,, 2011)
Mismatched lovers and unexpected attraction catch fire in this timeless Regency romance by the New York Times bestselling author. Forced to wed to keep her inheritance, independent Lady Jocelyn Kendal finds an outrageous solution: she proposes marriage to Major David Lancaster, an officer dying from his Waterloo wounds. In return for making her his wife, she will provide for his governess sister. But after the bargain is struck and the marriage is made, the major makes a shocking, miraculous recovery. Though they agree to an annulment, such matters take time . . . time enough for David to realize he is irrevocably in love with his wife. Haunted by her past, Jocelyn refuses to trust the desire David ignites in her. She never counted on a real husband, least of all one who would entice her to be a real wife. But some bargains are made to be broken—and his skilled courtship is impossible to resist . . . Praise for Mary Jo Putney "Putney's endearing characters and warm-hearted stories never fail to inspire and delight." —Sabrina Jeffries "A complex maze of a story twisted with passion, violence, and redemption. Miss Putney just gets better and better." —Nora Roberts "A gifted writer with an intuitive understanding of what makes romance work." —Amanda Quick "No one writes historical romance better." —Cathy Maxwell "Dynamite!" —Laura Kinsale

Not Quite a Wife (Lost Lords, ,, 2014)
From the bestselling author of Sometimes a Rogue. "Of all Putney's heroes, the Lost Lords are the most irresistible—bad boys who are so very good."—RT Book Reviews Marry in haste, repent at leisure. James, Lord Kirkland, owns a shipping fleet, half a London gaming house, and is a ruthlessly effective spymaster. He is seldom self-indulgent . . . except when it comes to the gentle, indomitable beauty who was once his wife. Laurel Herbert gave James her heart as an innocent young girl—until she saw him perform an act of shocking violence before her very eyes. That night she left her husband, and he let her go without a word of protest. Now, ten years later, a chance encounter turns passionate, with consequences that cannot be ignored. But as they try to rebuild what was broken, they must face common enemies and a very uncommon love . . . Praise for Mary Jo Putney and the Lost Lords series "Romance at its best!"—Julia Quinn "Intoxicating, romantic and utterly ravishing. . ."—Eloisa James "Putney's endearing characters and warm-hearted stories never fail to inspire and delight."—Sabrina Jeffries "Adventure, passion and pure reading pleasure!"—Jo Beverley "No one writes historical romance better."—Cathy Maxwell "Delivers captivating characters, an impeccably realized Regency setting, and a thrilling plot rich in action and adventure."—Booklist (starred review)

The Painter's Daughter (Recorded Books, Inc., Baker Publishing Group, 2016)
Sophie Dupont, daughter of a portrait painter, assists her father in his studio, keeping her own artwork out of sight. She often walks the cliffside path along the north Devon coast, popular with artists and poets. It's where she met the handsome Wesley Overtree, the first man to tell her she's beautiful. Captain Stephen Overtree is accustomed to taking on his brother's neglected duties. Home on leave, he's sent to find Wesley. Knowing his brother rented a cottage from a fellow painter, he travels to Devonshire and meets Miss Dupont, the painter's daughter. He's startled to recognize her from a miniature portrait he carries with him--one of Wesley's discarded works. But his happiness plummets when he realizes Wesley has left her with child and sailed away to Italy in search of a new muse. Wanting to do something worthwhile with his life, Stephen proposes to Sophie. He does not offer love, or even a future together, but he can save her from scandal. If he dies in battle, as he believes he will, she'll be a respectable widow with the protection of his family. Desperate for a way to escape her predicament, Sophie agrees to marry a stranger and travel to his family's estate. But at Overtree Hall, her problems are just beginning. Will she regret marrying Captain Overtree when a repentant Wesley returns? Or will she find herself torn between the father of her child and her growing affection for the husband she barely knows?

Water for Elephants: A Novel (HighBridge, Algonquin Books, 2007)
Over 10,000,000 copies in print worldwide #1 New York Times Bestseller A Los Angeles Times Bestseller A Wall Street Journal Bestseller A Newsday Favorite Book of 2006 A USA Today Bestseller A Major Motion Picture starring Reese Witherspoon, Robert Pattinson, and Christoph Waltz Jacob Janowski's luck had run out--orphaned and penniless, he had no direction until he landed on a rickety train that was home to the Benzini Brothers Most Spectacular Show on Earth. A veterinary student just shy of a degree, he was put in charge of caring for the circus menagerie. It was the Great Depression and for Jacob the circus was both his salvation and a living hell. There he met Marlena, the beautiful equestrian star married to August, the charismatic but brutal animal trainer. And he met Rosie, an untrainable elephant who was the great hope for this third-rate traveling show. The bond that grew among this group of misfits was one of love and trust, and ultimately, it was their only hope for survival. Sara Gruen is the #1 New York Times and USA Today bestselling author of At the Water's Edge,Water for Elephants, Ape House, Riding Lessons, and Flying Changes. Her works have been translated into forty-three languages and have sold more than ten million copies worldwide. Water for Elephants was adapted into a major motion picture starring Reese Witherspoon, Rob Pattinson, and Christoph Waltz in 2011. She lives in western North Carolina with her husband and three sons, along with their dogs, cats, horses, birds, and the world's fussiest goat. Only three people were left under the red and white awning of the grease joint: Grady, me, and the fry cook. Grady and I sat at a battered wooden table, each facing a burger on a dented tin plate. The cook was behind the counter, scraping his griddle with the edge of a spatula. He had turned off the fryer some time ago, but the odor of grease lingered. The rest of the midway-so recently writhing with people-was empty but for a handful of employees and a small group of men waiting to be led to the cooch tent. They glanced nervously from side to side, with hats pulled low and hands thrust deep in their pockets. They wouldn't be dis appointed: somewhere in the back Barbara and her ample charms awaited. The other townsfolk-rubes, as Uncle Al called them-had already made their way through the menagerie tent and into the big top, which pulsed with frenetic music. The band was whipping through its repertoire at the usual earsplitting volume. I knew the routine by heart-at this very moment, the tail end of the Grand Spectacle was exiting and Lottie, the aerialist, was ascending her rigging in the center ring. I stared at Grady, trying to process what he was saying. He glanced around and leaned in closer. "Besides," he said, locking eyes with me, "it seems to me you've got a lot to lose right now." He raised his eyebrows for emphasis. My heart skipped a beat. Thunderous applause exploded from the big top, and the band slid seamlessly into the Gounod waltz. I turned instinctively toward the menagerie because this was the cue for the elephant act. Marlena was either preparing to mount or was already sitting on Rosie's head. "I've got to go," I said. "Sit," said Grady. "Eat. If you're thinking of clearing out, it may be a while before you see food again." That moment, the music screeched to a halt. There was an ungodly collision of brass, reed, and percussion-trombones and piccolos skidded into cacophony, a tuba farted, and the hollow clang of a cymbal wavered out of the big top, over our heads and into oblivion. Grady froze, crouched over his burger with his pinkies extended and lips spread wide. I looked from side to side. No one moved a muscle-all eyes were directed at the big top. A few wisps of hay swirled lazily across the hard dirt. "What is it? What's going on?" I said. "Shh," Grady hissed.

Under an Outlaw Moon: A Novel (ECW Press, 2021)
Meet Depression-era newlyweds Bennie and Stella. He's reckless, she's naive. Longing for freedom from tough times, they rob a bank, setting off a series of events that quickly spin out of their control Under an Outlaw Moon is based on the true story of Depression-era bank robbers Bennie and Stella Mae Dickson. She's a teenage outsider longing to fit in. He's a few years older and he's trouble. They meet at a local skating rink and the sparks fly. They marry and Stella dreams of a nice house with a swing out back, while Bennie figures out how to get enough money to make it happen. Setting his sights on the good life, he decides to rob a bank. Talking Stella into it, he lays out his plan and teaches her to shoot. The newlyweds celebrate her 16th birthday by robbing a local bank. They pull it off, but the score is small, and Bennie realizes the money won't last long, so he plans a bigger robbery. What lays ahead is more than, either of them bargained for. After J. Edgar Hoover finds out they crossed state lines, he declares them public enemies, number one and two, wanted dead or alive. So much for the good life. The manhunt is on, and there's little room for them to run. Meet Depression-era newlyweds Bennie and Stella. He's reckless, she's naive. Longing for freedom from tough times, they rob a bank. Soon they top the FBI's "Most Wanted" list. So much for the good life.

Sometimes a Rogue (Lost Lords, ,, 2014)
The fifth Lost Lords novel "delivers captivating characters, an impeccably realized Regency setting, and a thrilling plot rich in action and adventure" (Booklist, starred review). Even the most proper young lady yearns for adventure. But when the very well-bred Miss Sarah Clarke-Townsend impulsively takes the place of her pregnant twin, it puts her own life at risk. If the kidnappers after her sister discover they've abducted Sarah instead, she will surely pay with her life . . . Rob Carmichael survived his disastrous family by turning his back on his heritage and becoming a formidable Bow Street Runner with a talent for rescuing damsels in distress. But Sarah is one damsel who is equal to whatever comes. Whether racing across Ireland with her roguish rescuer or throwing herself into his arms, she challenges Rob at every turn. "Putney's reputation as one of the finest writers of Regency romance is well deserved. She never shies away from different plots or atypical characters and writes wildly exciting adventure romances. She's done it all again in the marvelous, emotional and thrilling fifth book in the Lost Lords series."—RT Book Reviews (Top Pick) Praise for Mary Jo Putney and the Lost Lords series "Romance at its best!"—Julia Quinn "Intoxicating, romantic and utterly ravishing. . ."—Eloisa James "Putney's endearing characters and warm-hearted stories never fail to inspire and delight."—Sabrina Jeffries "Adventure, passion and pure reading pleasure!"—Jo Beverley "No one writes historical romance better."—Cathy Maxwell